2006
DOI: 10.1361/105994906x117198
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Environment Effects on the Oxidation of Metallic Interconnects

Abstract: Metallic interconnects in solid oxide fuel cells are exposed to a dual environment: fuel on one side (i.e. H 2 gas) and oxidizer on the other side (i.e. air). It has been observed that the oxidation behavior of thin stainless steel sheet in air is changed by the presence of H 2 on the other side of the sheet. The resulting dual environment scales are flaky and more friable than the single environment scales. The H 2 disrupts the scale on the air-side. A model to explain some of the effects of a dual environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 8 publications
3
41
0
2
Order By: Relevance
“…Exposure time was limited to 500 h and 300 h [17e19]. Holcomb et al studied dual exposure of the austenitic steel 316L and found that heavy corrosion was taking place after 100 h at 700 C. It was caused by the diffusion of oxygen and hydrogen in the alloy and the formation of steam in the metal alloy near the oxide layer, which formed a thick and porous oxide layer [20].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure time was limited to 500 h and 300 h [17e19]. Holcomb et al studied dual exposure of the austenitic steel 316L and found that heavy corrosion was taking place after 100 h at 700 C. It was caused by the diffusion of oxygen and hydrogen in the alloy and the formation of steam in the metal alloy near the oxide layer, which formed a thick and porous oxide layer [20].…”
Section: Introductionmentioning
confidence: 99%
“…1 From the development of interconnects in solid fuel cells (SOFC), it is known that dual atmosphere environments influence corrosion behavior, increase the oxide scale thickness, and can alter the oxide phases. [2][3] Operations at higher pressures are planned in future power plants to increase the efficiency and to make sequestration of the CO 2 possible. However, an accelerated corrosion under dual environments on the air side could reduce the wall thickness of power plant components faster than expected and shorten the life time of critical sections.…”
Section: Introductionmentioning
confidence: 99%
“…However, results obtained under dual environments are significantly different than those for a single atmosphere exposure or than these in dual atmospheres, such as air/air. [2][3][4] Tubes for power plants were investigated by Nakagawa, et al, in a steam/air dual environment at 600°C for up to 2,000 h. 5 All steels showed greatly increased corrosion rates on the air sides under conditions of steam/air dual environments compared to the oxidation in air under single atmosphere conditions. The oxides that formed on the steam side consisted of spinel with iron and chromium.…”
Section: Introductionmentioning
confidence: 99%
“…These studies, however, were usually carried out using single atmosphere exposure conditions (i.e., either an oxidizing [5,[13][14][15][16] or reducing environment [17], and were presumably based on the assumption that oxidation behavior in either an oxidizing or reducing environment essentially remained identical to the scale growth and corrosion occurring on the air or fuel side of the material when it experiences dual atmosphere conditions. However, previous and recent investigation of various stainless steels, including 304, 316, 430, Crofer 22 APU, etc., under hydrogen/air dual exposures have indicated that the oxidation/corrosion behavior of the steels under the dual atmosphere exposures could be very different from that under a single atmosphere exposure [18][19][20][21][22][23][24]. In particular, the oxidation/corrosion behavior observed on the air side of the air/hydrogen dual exposure sample differed significantly from the behavior in a single air exposure, while the oxidation/corrosion behavior on the hydrogen side of the dual exposure sample was comparable to that when exposed to the hydrogen fuel on both sides.…”
Section: Introductionmentioning
confidence: 99%